MFRP variations cause nanophthalmos in five Chinese families with distinct phenotypic diversity - Li, Zhen; Ma, Runqing; Ma, Meijiao; Xiao, Xue; Qi, Xiaolong; Ma, Hongjuan; Sheng, Xunlun; Rong, Weining (Frontiers in Genetics, 2024)
Purpose: The objective of this study is to identify the genetic cause of nanophthalmos in the affected families and analyze the clinical phenotype of nanophthalmos with MFRP gene variation(Microphthalmia, isolated; OMIM#611040 and Nanophthalmos 2;OMIM#609549, respectively).Comprehensive ophthalmic examinations were performed on participants to confirm the phenotype. The genotype was identified using whole exome sequencing, and further verified the results among other family members by Sanger sequencing. The normal protein structure was constructed using Alphafold. Mutant proteins were visualized using pymol software. Pathogenicity of identified variant was determined by in silico analysis and the guidelines of American College of Medical Genetics and Genomics (ACMG). The relationship between genetic variants and clinical features was analyzed. Results: Five nanophthalmos families were autosomal recessive, of which four f amilies carried homozygous variants and one family had compound heterozygou s variants in the MFRP gene. Both family 1 and family 3 carried the homozyg ous missense variant c.1486G>A (p.Glu496Lys) in the MFRP gene(Clinvar:SCV 005060845), which is a novel variant and evaluated as likely pathogenic accord ing to the ACMG guidelines and in silico analysis. The homo zygous nonsense variant c.271C>T (p.Gln91Ter)(Clinvar:SCV005060846) of the MFRP gene was detected in family 2, presenting shallow anterior chamber in both eyes, pigmentation of peripheral retina 360°from the equator to the serrat ed rim showing a clear demarcation from the normal retina in the form of stri ps. Family 4 proband carried the homozygous missense variant c.1411G>A (p.V al471Met) in the MFRP gene(Clinvar:SCV005060847), family 5 proband carried compound heterozygous missense variants c.1486G>A (p.Glu496Lys) and c.602 G>T (p.Arg201Leu) in the MFRP gene(Clinvar:SCV005060848), which is a no vel variant and evaluated as likely pathogenic according to the ACMG guidelin es and in silico analysis, and they all presented clinically with binocular angleclosure glaucoma, family 4 also had retinal vein occlusion in the right eye dur ing the follow-up. Conclusion: In this study, pathogenic variants of the MFRP gene were detected in five nanophthalmos families, including two novel variants. It also revealed a distinct phenotypic diversity among 5 probands harboring variants in the MFRP gene.